TREATMENT OF UNSTABLE DISTAL RADIUS FRACTURES BY PERCUTANEOUS PINNING AND PLASTER CAST IMMOBILIZATION - Muhammad shafiq Khan; Mohammad Ali Shah; Mian Amjad Ali; Shakil Ahmad Shah; Irfan Aziz (Gomal Journal of Medical Sciences, 2015)
Background: Treatment of displaced fractures of the distal end of radius has changed over the course of time. This study was conducted to determine the functional and radiological outcome of percutaneous pinning followed by plaster cast for unstable fractures of distal aspect of radius. Material & Methods: This descriptive study was conducted at DHQ Teaching Hospital D.I.Khan, from April 2009 to September 2012. A total of 32 patients with mean age of 58 years having unstable fractures of distal radius were included in the study. They were all operated within 48 hours by closed reduction and percutaneous K-wire fixation and POP cast. Mean follow-up was 28 weeks (range 22-32 weeks) during which patients were assessed both radiologically and functionally using criteria of Jakim et al. Results: On radiological assessment, mean volar tilt was corrected to 3° (normal 11°). Mean radial height was 10 mm (normal 12 mm) and mean radial inclination was 22o (normal 23°). On functional assessment, 16 (50%) patients showed excellent, 12 (38%) showed good results while 4 (12%) gave fair outcome. Poor result was not encountered in any patient. Conclusion: Percutaneous K-wire fixation and plaster cast immobilization can restore radiographic parameters to nearly normal values and provide good functional results without much complication.